GALVALUM ROOF QUALITY CONTROL ANALYSIS TO MINIMIZE DEFECTS USING THE FMECA (FAILURE MODE EFFECT AND CRITICALITY ANALYSIS) AND RCA (ROOT CAUSE ANALYSIS) METHODS AT PT TRISAKTI JAYA - Rangga Bustanul Firdaus; Wiwik Sulistiyowati (Antis Publisher, 2025)
Objective: This study aims to identify and solve the problem of product defects that occur at PT. Trisakti Jaya, a galvalume production company located in the Margo Mulyo Permai warehouse block C-6 Surabaya, which has 6 long vehicles and approximately 200 employees. These defects have reduced customer satisfaction and caused financial losses for the company. Method: The research employs the FMECA (Failure Mode Effect and Criticality Analysis) and RCA (Root Cause Analysis) methods. The FMECA method explains how the percentage of product defects can occur and what percentage arises after using this method, while the RCA method determines how the most effective solutions to problems can be obtained to help the company find the best corrective actions. Result: The results show that tears and dents are the highest types of defects, with the highest defect rate occurring in December. This is because the defect data exceeded the upper limit of the control chart, where the tear UCL (Upper Control Limit) is 2470 while the defect data is 2451, and the dent UCL is 3700 while the defect data is 3677. The tear defect is mainly caused by a lack of care when using the machine and minimal lighting in several warehouse corners. Novelty: The study provides a practical improvement recommendation by reminding operators about proper cutting machine operation and repairing lighting in less bright warehouse areas, offering a targeted and data-driven approach to reduce recurring defects in the galvalume production process.